Analysis the Effect of Variation Permanent Magnet and Winding on BLDC Motor Performance Using ANSYS Maxwell Simulation - Muhamad Yusron Nur Arna; Dony Hidayat Al-Janan (AEEJ : Journal of Automotive Engineering and Vocational Education, 2025)
One of the driving components of electric vehicles that are often used is Brushless (BLDC) motors which have advantages such as high efficiency, large torque density, and precise speed control. This study aims to evaluate the effect of variations in permanent magnet type and stator winding configuration on the performance of Brushless DC (BLDC) motors. Two types of permanent magnets, NdFe35 and SmCo24, are compared based on their electromagnetic characteristics, such as torque, rotational speed, efficiency, and current consumption. In additional, the stator winding parameters were varied, including wire diameters between 1.3 mm and 1.6 mm and the number of conductors per slot between 14 and 23. The simulation results conducted using ANSYS Maxwell show that the configuration combining NdFe35, an optimal number of 14 conductors per slot, and a large wire diameter of 1.6 mm delivers the best performance, with a maximum torque of 325 Nm, maximum power of 2.91 kW, efficiency of 79%, and a speed of 1241.5 rpm. Although the current consumption is high, the resulting power and torque performance are proportional.